Learning Design of Indonesian Phonology Based on Digital Learning Management System - Muhammad Oky Fardian (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The 4.0 industrial revolution that occurs today, demands the changes of learning process in universities towards learning based on digital. The form of digitalization of the learning process will later penetrate the boundaries of space and time that have been blocking the interaction between the lecturers and the students. This simple writing, then will describe the design of the digital learning process in colleges. The digitalization in this paper means an android-based learning design utilizing software/learning management system (LMS) for activities in the network (online) in Indonesian phonology courses. Some features that can be utilized in managing LMS-based learning are: a) Courses, with courses menu, the users can create new classes, join classes that have already existed or browse through the predefined class list. b) Groups which functions like the wall messages of the group members and can also post on the wall messages. When joining a group, the users can search for parts of the group that the users want. c) Resources are to maintain, to track the documents, files and images that users upload in the class. d) Recent Activity is to display the latest news contained in the account. e) Calendar, to display the calendar page that was posted earlier in the Recent Activity. f) Messages are to send messages or view the messages among the fellow users, and g) People is to be able to see a list of the users in a class.